2012
DOI: 10.1016/j.comptc.2012.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The structural investigation on small methane clusters described by two different potentials

Abstract: Structures of molecular clusters have not been well elucidated. In the present study, a fundamental cluster (CH 4 ) n (n ≤ 40) was theoretically investigated with two potentials; one is a well-known potential called OPLS and the other is a Morse potential obtained from ab initio calculations of the methane dimer. The global minima of methane clusters were searched with the heuristic method combined with geometrical perturbations. The local structure analysis of the global-minimum geometries of the clusters sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…A possible reason is that CH 4 molecules form small clusters because of intermolecular interactions caused by the Lennard-Jones potential, which was demonstrated by theoretical calculations. [41] Thus, CH 4 cannot freely pass through the pores of the M-DNL-6 adsorbent, and the true adsorption equilibrium is not reached. Palomino et al observed similar phenomena when they studied CH 4 adsorption on the RHO zeolite.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…A possible reason is that CH 4 molecules form small clusters because of intermolecular interactions caused by the Lennard-Jones potential, which was demonstrated by theoretical calculations. [41] Thus, CH 4 cannot freely pass through the pores of the M-DNL-6 adsorbent, and the true adsorption equilibrium is not reached. Palomino et al observed similar phenomena when they studied CH 4 adsorption on the RHO zeolite.…”
Section: Adsorption Isothermsmentioning
confidence: 99%
“…An alternative starting geometry also considered was the lowest-energy structure from a heuristic method to locate the global minimum on the OPLS potential energy surface. 41,42 In all cases except for the (CH 4 ) 4 cluster, the lower-symmetry starting structure produced stronger binding energies ( 37 The Cu−Cu distances in the Cu 2 O 8 units are slight too short, probably due to the absence of coordinated DMF and H 2 O molecules in the calculated structure. However, the Cu−O and cross-ring Cu−Cu distances are predicted very well.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…As a preliminary to the study of CH 4 binding in the Cu 24 ( m -BDC) 24 cage, the binding energies of CH 4 clusters were calculated. Symmetrical complexes were considered with D 3 d and S 4 symmetries (Figure ). An alternative starting geometry also considered was the lowest-energy structure from a heuristic method to locate the global minimum on the OPLS potential energy surface. , In all cases except for the (CH 4 ) 4 cluster, the lower-symmetry starting structure produced stronger binding energies (Table ). The binding energies of the CH 4 clusters are in good agreement with previous work employing force field and DFT calculations (Table ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the neutral (CH 4 ) 4 tetramer, rhombic and pyramidal isomers (Figure 2) are computed to be stable in agreement with those of Takeuchi. 35 For (CH 4 ) 4 + , a proton is shared between two methane units. This charge transfer complex may dissociate later to produce CH 3 + CH 5 (CH 4 ) 2 + .…”
Section: Resultsmentioning
confidence: 99%